Evaluación de la gestión administrativa para la mejora del servicio que brinda el seguro social campesino del sitio rancho viejo “Chone” - Moreira García, Omar Antonio (2019)
The purpose of this research was to evaluate the administrative management of the Rural Social Security Farm Rancho Viejo de Chone, which was carried out through the specific objectives, having first of all in the investigation identify the processes of public server in the administrative management of the Rural Social Security of Rancho Viejo, therefore this objective helped to know the functions of the personnel that works in the dispensary, consecutively in second place, instruments are applied for the evaluation of the quality of the service in the administrative management of the Social Insurance Farmer of Rancho Viejo, which was known by the doctor in charge of the dispensary for the improvement of the same methods of verification of compliance for public servers had been implemented, in addition systems have been made in order to promote the quality of the service. However, it should be noted that the dispensary has problems in terms of lack of medication. Also, a survey was apply to the affiliate, so it is of vital importance to mention that they contributed to help with the investigation and in turn to demonstrate about the administrative management of the dispensary. And finally, it is proposed to carry out an improvement plan with strategies that contribute to the improvement of the administrative management of the Rural Social Security of Rancho Viejo.